The Pedagogical Design of Eco-Theology-Based Science Worksheets in Elementary Schools in Mataram City - Hamzan; Tutik Dinur Rofiah (Universitas Pendidikan Ganesha, 2026)
The delivery of material still dominates science learning, so the integration of ecological values into contextual and reflective learning experiences has not been fully implemented. This study aims to analyze the construction, implementation, and meaning of ecotheology-based Science Student Worksheets (LKPD) for developing critical and creative thinking skills and environmental awareness among elementary school students. This study uses a qualitative approach with a case study design. The research subjects were 21 participants, comprising 3 school principals, 6 high school science teachers, and 12 students in grades IV–VI, who were purposively selected. Data were collected through semi-structured interviews, observations, and document analysis, using interview guidelines, observation sheets, and document analysis sheets that were validated through expert judgment. Data analysis was carried out using thematic analysis through the stages of data introduction, coding, theme development, theme review, theme definition, and preparation of narrative results. The results of the study indicate that ecotheology-based Science Student Worksheets are designed as a pedagogical space that integrates scientific knowledge, khilāfah, amanah, and mizān values, as well as students' ecological experiences, thereby supporting the contextual development of critical and creative thinking skills and environmental care attitudes. The conclusion is that ecotheology-based Science Student Worksheets are a pedagogical approach that holistically integrates science learning with ecological values. The implications of this study provide a conceptual basis for developing science teaching materials that are reflective, contextual, and oriented towards sustainable environmental education in elementary schools.